Soil chemical properties in abandoned Mediterranean cropland after succession and oak reforestation - Cuesta, B.; Rey Benayas, J. M.; Gallardo, A.; Villar-Salvador, P.; González-Espinosa, M. (Acta Oecologica, 2012)
Large extents of cropland have been abandoned in recent decades and more may be abandoned in the near future. These may undergo secondary succession or reforestation. We experimentally tested the response of soil chemical properties to secondary succession (old ﬁeld) and to Quercus ilex plantation (reforested cropland) in a Mediterranean cropland that was abandoned 13 years ago. We also evaluated the relevance of previous reforestation management (four combinations of presence and absence of irrigation and shading) in addition to current environmental conditions (herbaceous community and cover of oak canopy) on soil chemistry in the reforested cropland. Carbon and NH4 þ eN concentrations and availability of mineral N were higher in the reforested cropland than in the old ﬁeld. However, soil pH, total N, P, K and NO3 eN concentrations, mineralization rates, and available PO4 3 eP were similar in the reforested cropland as well as in the old ﬁeld. Previous reforestation management practices, particularly irrigation, and current environmental conditions, mostly biomass and composition of the herbaceous community, affected soil chemistry. Irrigation increased K and P concentrations and NH4 þ eN availability. This study highlights the overall slow dynamics of soil chemistry in Mediterranean ecosystems, which has resulted in little variation of soil properties in reforested cropland after more than a decade. Reforestation can accelerate the recovery of some soil properties of abandoned cropland in comparison with secondary succession, but these effects will be more noticeable in longer time periods.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: ammonium; Inorganic nitrogen; nitrate; Old ﬁelds; Quercus ilex; Soil fertility; Tree planting

Life-history traits in an evergreen Mediterranean oak respond differentially to previous experimental environments - Benayas, J. M. R.; Cuesta, Bárbara; Villar-Salvador, P.; Jáuregui, Pedro (Web Ecology, 2008)
Living organisms respond both to current and previous environments, which can have important consequences on population dynamics. However, there is little experimental evidence based on long-term field studies of the effects of previous environments on the performance of individuals. We tested the hypothesis that trees that establish under different environmental conditions perform differently under similar post-establishment conditions. We used the slow-growing, evergreen Mediterranean oak Quercus ilex subsp. rotundifolia as target species. We analyzed the effects of previous environments, competition effects and tradeoffs among life-history traits (survival, growth, and reproduction). We enhanced seedling establishment for three years by reducing abiotic environmental harshness by means of summer irrigation and artificial shading in 12 experimental plots, while four plots remained as controls. Then these treatments were interrupted for ten years. Seedlings under ameliorated environmental conditions survived and grew faster during early establishment. During the post-management period, previous treatments 1) did not have any effect on survival, 2) experienced a slower above-ground growth, 3) decreased root biomass as indicated from reflectivity of Ground Penetration Radar, 4) increased acorn production mostly through a greater canopy volume and 5) increased acorn production effort. The trees exhibited a combination of effects related to acclimation for coping with abiotic stress and effects of intra-specific competition. In accordance with our hypothesis, tree performance overall depended on previous environmental conditions, and the response was different for different life-history traits. We recommend early management because it increased plot cover, shortened the time to attain sexual maturity and increased the amount of acorn production. Plots such as those assessed in this study may act as sources of propagules in deforested agricultural landscapes thus aiding natural establishment of new plants
Keywords: acorn production; canopy volume; competition; environmental conditions; Growth; management (voyant); shoot/root ratio

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading